KOMUNIKASI PENYULUHAN BADAN KOORDINASI PENYULUHAN PROVINSI RIAU DALAM UPAYA MENINGKATKAN PRODUKSI PERTANIAN DI KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI - Lucia Desy Putri Pratama; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Extension activities in agriculture development act as a bridge that connects the practice run by peasant farmers with the knowledge and technology that is always evolving into the needs of farmers in Sentajo Kingdom . So that farmers can carry out practices that support farming , the farmers need information on innovation in agriculture . Such information can be obtained by farmers from PPL ( Agricultural Extension Field ) through the implementation of agricultural extension activities , the perpetrators of counseling required to work hard and sensitive to the community . This study aims to determine strategies that do extension in improving agricultural production in district Sentajo Raya .The method used in this study is a qualitative method that attempts to explain the phenomenon that occurs in accordance with the results obtained by setting 15 (fiveteen) of the study subjects as informants through purposive technique . The object of this study is the extension of communication coordination agency extension of Riau province in an effort to increase agricultural production in the district highway Sentajo Raya Kuantan Singingi of data based on information obtained through observation , interviews , and documentation . Technical analysis of the data in this study using interactive data model with data validity checking is done using the extension of participation and triangulation techniques.The results showed that the dimensions of the communicator with the limited number of extension workers are still not optimal in the provision of agricultural extension , and media dimensions are available but underused . While the dimensions of the message , the communicant and the effects already performing as it should . For the dimensions of empowerment : the ability and skills have been applied and be realized by extension agents and farmers. However, for the dimensions of knowledge , there is the educational level of farmers are still low .Key words: comunications, counseling, instructor agriculture